(3GdQSGdI GdYOOjIs - (3CMeO Hf YHO GdMdje Hf YHO GdSdGe GdMQGfj, Jbj GdOjf, GHf JjejI, CHh GdYHGS , J (B728 (3g` s ((3Ydi Hf MSf Hf eMeO GdMQGfi s)
(3ChdgG (B:s
(3GdMeO ddg SFdJ Cj GdCeQjf CaVd JdGhI GdbQBf Ch GdPcQ s
(3BNQgG (B:s
(3abO jchf NSQGfg CcKQ ef QHMg hbO jchf Cbd Ch CcKQ hGddg CYde s
(3Vef eLehY , JQJjHgG (B: 4s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B144s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdESdGejs